The God of Spinoza a philosophical study - Mason, Richard 1948-2006 (Cambridge University Press, 1997)
This book is the fullest study in English for many years on the role of God in Spinoza's philosophy. Spinoza has been called both a 'God-intoxicated man' and an atheist, both a pioneer of secular Judaism and a bitter critic of religion. He was born a Jew but chose to live outside any religious community. He was deeply engaged both in traditional Hebrew learning and in contemporary physical science. He identified God with nature or substance: a theme which runs through his work, enabling him to naturalise religion but - equally important - to divinise nature. He emerges not as a rationalist precursor of the Enlightenment but as a thinker of the highest importance in his own right, both in philosophy and in religion